2016
DOI: 10.1149/2.0151606jes
|View full text |Cite
|
Sign up to set email alerts
|

A Method for the Determination of Weak Acid Concentration Based on Electrochemical Reduction of Benzoquinone

Abstract: With the addition of a weak acid, a new prepeak occurs at a positive potential when quinone is reduced in an unbuffered solution. This prepeak was initially attributed to the protonation of a quinone anion radical. However, two prepeaks of the reduced quinone are detected in a solution containing dilute acetic acid and sodium dihydrogen phosphate. Evidently, the two prepeaks could not be assigned to the protonation of the quinone anion radical. In the unbuffered solution, the pH near the electrode surface incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Scheme 1 implies that the amount of the reduced BQ decides by that of proton donors (free acid) when the pH near the working electrode surface increases markedly [13]. We observed that the height of the new peak is proportional to the concentration of free acids but is independent of the BQ concentration [14]. Therefore, the weak acid concentration can be measured.…”
Section: Mechanism Of Measurement Of Free Acid Contentmentioning
confidence: 79%
See 1 more Smart Citation
“…Scheme 1 implies that the amount of the reduced BQ decides by that of proton donors (free acid) when the pH near the working electrode surface increases markedly [13]. We observed that the height of the new peak is proportional to the concentration of free acids but is independent of the BQ concentration [14]. Therefore, the weak acid concentration can be measured.…”
Section: Mechanism Of Measurement Of Free Acid Contentmentioning
confidence: 79%
“…The addition of HAc to the solution results in a new peak at about + 0.15 V. The new peak is caused by a drastic pH decrease near the electrode surface compared to the BQ solution at pH 6.98. Based on this, we have developed methods for the determination of acetic acid [14]. When the concentration of HAc is less than twice the concentration of BQ, and the value of the new peak current is linear with the concentration of HAc.…”
Section: Effect Of Hac On the Dpv Of Bq In Aqueous Solutionmentioning
confidence: 99%
“…When the protons provided by ATP, ADP and CTP were depleted, the pH of the electrode surface increased abruptly, which caused the formation of the peaks A 2 , A 3 , B 2 , B 3 , C 2 , and C 3 . Wang 27,28,34 revealed that the peak current was dependent on the proton donor concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The benzoquinones (BQ)/hydroquinone (BQH 2 ) couple is often studied in the context of proton-coupled electron transfer. 26 Some researchers [27][28][29] have utilized BQ/BQH 2 couples to determine acids by BQ reduction in an aqueous solution (Scheme 1). We constructed a new electrochemical method using bare glassy carbon electrodes to determine acid.…”
mentioning
confidence: 99%
See 1 more Smart Citation